BELT AND ROAD INITIATIVE (BRI) AND ITS IMPLICATION ON MARITIME SECURITY IN ASIA PACIFIC: CASE STUDY ON CHINA-AUSTRALIA TRADE COOPERATION - Muhammad Akbar (Kajian Asia Pasifik, 2019)
Belt and Road Initiative (BRI) or One Belt One Road (OBOR) first introduced by Xi Jinping on September 2013 in Kazakhstan, when he stated â€œSilk Road Economic Beltâ€, specifically. One month later, he stated the term â€œMaritime Silk Roadâ€ in Indonesia. OBOR is both a concept and a work plan that designed by China to connect towards Eurasia, Africa, and Oceania. The connections are both distance and political influence. Chinaâ€™s bargaining position on Australia is considered strong enough, and vice versa. Australia is important for China for its iron ore that exported to China. China will not put their position at a stake considering its 60% dependency of iron ore from Australia, based on the research by Professor Rory Medcalf from Australia National University (Medcalf 2017, 110). The complexity of the struggle for power in this region is increasing since Australia has been the ally of The United States of America (USA) to whom China is declaring Trade War. Chinaâ€™s expenditure and development of the Navy growing increasingly reflects the higher attention on maritime security. Political condition in Asia Pacific will be effected by this condition with the growing influence of the superpower of the South China Sea, the Peopleâ€™s Republic of China. This paper will explore about sea power in Asia Pacific and its relations with the growing and more advanced China-Australia relations. Keywords: OBOR (One Belt One Road), Maritime Security, Sea Power, Asia Pacific. Abstrak Istilah Belt and Road Initiative (BRI) atau dikenal juga dengan jargon One Belt One Road (OBOR) pertama kali digaungkan oleh Xi Jinping pada bulan September 2013 di Kazakhstan, ia mengucapkan â€œSilk Road Economic Beltâ€, secara spesifik. Sebulan kemudian, Ia menyinggung konsep â€œMaritime Silk Roadâ€ dalam kunjungannya ke Indonesia (Davies, 2016, 218). OBOR adalah sebuah konsep, sekaligus juga workplan yang dirancang sedemikian rupa oleh China untuk mendekatkannya dengan Eurasia, Afrika, dan Oceania. Dekat dalam artian keterhubungan melalui kemudahan transportasi, dan dekat secara pengaruh (political influence). Tulisan ini akan mengambil studi kasus kerja sama perdagangan yang dilakukan antara China dan Australia. Posisi tawar China terhadap Australia cukup kuat, dan begitu pula sebaliknya. Australia diunggulkan dengan komoditi biji besi yang diekspor ke China, sehingga membuat China memiliki ketergantungan terhadap Australia. Professor Rory Medcalf dari Australia National University (ANU) mengatakan bahwa China tidak akan mempertaruhkan hubungan perdagangannya dengan Australia, mengingat dependensi China terhadap impor biji besi dari Australia sebesar 60% (Medcalf 2017, 110). Australia adalah sekutu Amerika Serikat (AS) yang kini sedang dalam kondisi perang dagang dengan China, membuat hubungan diantara negara-negara ini menjadi kompleks. Anggaran belanja pertahanan dan percepatan pertumbuhan Armada Laut China cenderung meningkat, sehingga dapat disimpulkan adanya keseriusan dalam hal peningkatan keamanan maritim (maritime security). Kondisi politik regional di kawasan Asia Pasifik akan terdampak atas kedigdayaan maritim China di kawasan. Tulisan ini akan membahas mengenai Sea Power di kawasan Asia Pasifik dan kaitannya dengan hubungan dagang China-Australia yang semakin intens. Kata kunci: OBOR (One Belt One Road), Keamanan Maritim, Sea Power, Asia Pacific